Molecular detection of Citrus exocortis viroid (CEVd), Citrus viroid-III (CVd-III), and Citrus viroid-IV (CVd-IV) in Palestine - Aswar Abualrob; Osama Alabdallah; Raied Abou Kubaa; Sabri M. Naser; Raed Alkowni (Scientific Reports, 2024)
Abstract Citrus hosts various phytopathogens that have impacted productivity, including viroids. Missing data on the status of viroids in citrus in Palestine were not reported. This study was aimed to detect any of Citrus exocortis viroid (CEVd), Citrus viroid-III (CVd-III), and Citrus viroid-IV (CVd-IV) in the Palestinian National Agricultural Research Center (NARC) germplasm collection Field inspections found symptoms such as leaf epinasty; vein discoloration, and bark cracking on various citrus varieties. RT-PCR revealed a significant prevalence of CVd-IV; CEVd and CVd-III (47%, 31%, and 22%; respectively). CVd-III variants with 91.3% nucleic acid sequence homology have been reported. The sequence of each viroid were deposited in GenBank as (OP925746 for CEVd, OP902248 and OP902249 for CVd-III-PS-1 and -PS-2 isolates, and OP902247 for CVd-IV). This was the first to report three of citrus viroids in Palestine, appealing to apply of phytosanitary measures to disseminate healthy propagating materials free from viroids.